(untitled) (قضايا سياسية, 2022)
This study discusses the geopolitical dimensions of the Iraqi defense diplomacy and the mechanisms that allow it to move within a strategy whose main objective is to renew Iraq's effectiveness in the Middle East region.Through his defense diplomacy’s visions in charting his behavior towards his foreign relations by creating a space of joint cooperation with other countries as urgent strategic priorities, based on the criterion of openness to multiple circles and leading to the promotion of national reconciliation, achieving its strategic goals and facing security challenges. The study concludes that defense diplomacy represented a qualitative shift in the paths of the Iraqi foreign policy approach, especially as it seeks to create a diplomatic act to obtain international support to support Iraq's efforts to develop its military and security capabilities. Defence diplomacy has become an increasingly common tool that States use today to advance their national interests. The term "defence diplomacy" was first officially used by the British Ministry of Defence in the 1990s, a term used for many cooperative military activities conducted with other countries where there is no generally agreed definition or even a widely used definition of the term. But it is common to emphasize the peaceful use of the army (equipment, personnel and knowledge) to build trust and goodwill, which excludes any use of force. In this regard, it can be considered a subset of soft power, through which the practitioner seeks to change the behavior of other actors in the international system to secure their national interests.